Evidence for the Context Dependence of the Side-Effect Effect - Lau, Stephan (Journal of cognition and culture, 2016)
In four experiments involving 565 German speakers we tested several hypotheses about possible determinants of the side-effect effect (see), which consists of judging foreseen bad, but not good, side-effects of actions as intentionally produced. Experiment 1 failed to find intentionality ascriptions for bad side-effects for the majority of the participants in two different scenarios and obtained no consistent support for two hypothesized social-cognitive determinants of the see, the agent’s attitude and the mode of effect description. Experiment 2 replicated the see in the original ceo scenario, but again found no evidence that the effect was influenced by the agent’s attitude towards the side-effect. The see was also not influenced by a manipulation of the moral quality of the agent’s primary goal. Experiment 3 investigated six additional scenarios used in previous studies and again obtained clear evidence for the see only in the ceo scenario. In addition, Experiment 3 demonstrated that judgments of both intent and intentionality strongly increased if the original side-effect was described as a means to the agent’s primary goal, or as an independently pursued goal. Taken together, the findings suggest that for German speakers, the see depends on the specifics of the scenario content and is difficult to obtain outside the original ceo scenario. Consistent with these conclusions, Experiment 4 documented parallel difficulties replicating the “means effect”, an analogue of the see on the level of means, but replicated the see in a scenario closely modeled after the original ceo scenario.